“Efecto de la suplementación con lactosuero suministrados en el agua de bebida a pollos broiler en la etapa de crecimiento-acabado” - Lozano Chuquizuta, Max Roland (2014)
One of the economic activities that has experienced explosive growth and development, in recent years, is the poultry activity, which nowadays is the most important activity of the agricultural sub-sector, representing more than 50% of the livestock GDP, 22% of agricultural GDP and 1.8% of national GDP. This is reflected in the consumption per capita of 32.3 kg/inhabitant to 2010, (Minag 2011). In addition to be generating of employment, has also high incidence in the development of other activities agricultural or industrial, related of great impact economic for the country. It is noteworthy, that the importance of the poultry activity lies in its high level of technological development, with continuous developments and improvements in productive indicators (genetics, equipment, food and health) showing a sustained growth in recent years. It also helps to reduce malnutrition, because of increased consumption in the daily diet protein sources...